The Determinants of Bank Stability: An Empirical Investigation in Southeast Asia - Niken Novita Sari; Barianto Nurasri Sudarmawan (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This research aimed to examine the effect of institutional quality, financing growth, and earnings management on the stability of Islamic banks in Southeast Asia for the 2014-2021 period. The sampling technique used was purposive sampling and received 11 Islamic commercial banks from Brunei Darussalam, Indonesia, and Malaysia. Data sources were obtained from each bank's financial statements and the World Bank's statements. The analysis method used was panel data regression analysis with Eviews 12 software. The results showed that the quality of institutions and the growth of financing had a significant effect on the stability of banks proxied by the Z-Score. The quality of institutions has a positive influence, while the growth of financing has a negative effect on banks' stability. Furthermore, the variables of earnings management have no significant impact on the stability of the bank. This research was limited to a sample of countries in Southeast Asia, so it is expected to be a reference for improving the quality of institutions to support banking performance. The implications of this study are expected to be an evaluation for banks to pay more attention to their policies in financing expansion and improve the quality of financial statements to minimize earnings management practices whose existence does not affect bank stability. Keywords: Bank stability, institutional quality, banking performance, financing   ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh kualitas institusi, pertumbuhan pembiayaan dan manajemen laba terhadap stabilitas bank syariah di Asia Tenggara periode 2014-2021. Teknik pengambilan sampel menggunakan metode purposive sampling dan diperoleh 11 bank umum syariah dari negara Brunei Darussalam, Indonesia dan Malaysia. Sumber data diperoleh dari laporan keuangan masing-masing perbankan dan laporan World Bank. Metode analisis yang digunakan ialah analisis regresi data panel dengan software Eviews 12. Hasil penelitian menunjukkan bahwa kualitas institusi dan pertumbuhan pembiayaan berpengaruh secara signifikan pada stabilitas bank yang diproksikan dengan Z-Score. Kualitas institusi memiliki pengaruh yang positif sedangkan pertumbuhan pembiayaan berpengaruh negatif pada stabilitas bank. Selanjutnya, variabel manajemen laba tidak berpengaruh secara signifikan pada stabilitas bank. Penelitian ini terbatas pada sampel negara di Asia Tenggara, sehingga diharapkan dapat menjadi referensi dalam meningkatkan kualitas institusi untuk menunjang kinerja perbankan. Implikasi dari penelitian ini diharapkan dapat menjadi evaluasi bagi perbankan untuk lebih memperhatikan kebijakannya dalam ekspansi pembiayaan dan meningkatkan kualitas laporan keuangan guna meminimalisir praktik manajemen laba yang keberadaanya tidak mempengaruhi stabilitas bank. Kata Kunci: Stabilitas Bank, Kualitas Institusi, Kinerja Perbankan, Pembiayaan